Attenuation of cardiac dysfunction in polymicrobial sepsis by microRNA-146a is mediated via targeting of IRAK1 and TRAF6 expression - Gao, Ming (J Immunol, 2015)
Cardiac dysfunction is a major consequence of sepsis/septic shock and contributes to the high mortality of sepsis. Innate and inflammatory responses mediated by Toll-like receptors (TLRs) play a critical role in sepsis-induced cardiac dysfunction. MicroRNA-146 was first identified as a negative regulator in innate immune and inflammatory responses induced by LPS. This study examined whether miR-146a will have a protective effect on sepsis-induced cardiac dysfunction. Lentivirus expressing miR-146a (LmiR-146a) or lentivirus expressing scrambled miR (LmiR-control) were delivered into the myocardium via the right carotid artery. Seven days after transfection, mice were subjected to CLP. Untransfected mice were also subjected to CLP-induced sepsis. Cardiac function was examined by echocardiography before and 6 h after CLP. In vitro studies showed that increased miR-146a levels suppresses LPS-induced IκBα phosphorylation and inflammatory cytokine production in both H9C2 cardiomyocytes and J774 macrophages. In vivo transfection of LmiR-146a attenuated sepsis-induced cardiac dysfunction. The values for EF% and FS% in LmiR-146a transfected CLP mice were significantly greater than in untransfected CLP control. LmiR-146a transfection prevented sepsis-induced NF-κB activity, suppressed IRAK and TRAF6 expression in the myocardium, and attenuated sepsis-induced inflammatory cytokine production in both plasma and peritoneal fluid. In addition, LmiR-146a transfection decreased sepsis-induced infiltration of neutrophils and macrophages into the myocardium. LmiR-146a can also transfect macrophages in the periphery. We conclude that miR-146a attenuates sepsis-induced cardiac dysfunction by preventing NF-κB activation, inflammatory cell infiltration, and inflammatory cytokine production via targeting of IRAK and TRAF6 in both cardiomyocytes and inflammatory monocytic cells.